Bioengineered 3D Glial Cell Culture Systems and Applications for Neurodegeneration and Neuroinflammation. (June 2017) - Watson, P. Marc D.; Kavanagh, Edel; Allenby, Gary; Vassey, Matthew
Neurodegeneration and neuroinflammation are key features in a range of chronic central nervous system (CNS) diseases such as Alzheimer's and Parkinson's disease, as well as acute conditions like stroke and traumatic brain injury, for which there remains significant unmet clinical need. It is now well recognized that current cell culture methodologies are limited in their ability to recapitulate the cellular environment that is present in vivo, and there is a growing body of evidence to show that three-dimensional (3D) culture systems represent a more physiologically accurate model than traditional two-dimensional (2D) cultures. Given the complexity of the environment from which cells originate, and their various cell–cell and cell–matrix interactions, it is important to develop models that can be controlled and reproducible for drug discovery. 3D cell models have now been developed for almost all CNS cell types, including neurons, astrocytes, microglia, and oligodendrocyte cells. This review will highlight a number of current and emerging techniques for the culture of astrocytes and microglia, glial cell types with a critical role in neurodegenerative and neuroinflammatory conditions. We describe recent advances in glial cell culture using electrospun polymers and hydrogel macromolecules, and highlight how these novel culture environments influence astrocyte and microglial phenotypes in vitro, as compared to traditional 2D systems. These models will be explored to illuminate current trends in the techniques used to create 3D environments for application in research and drug discovery focused on astrocytes and microglial cells.